Karyotype Evolution and Genomic Organization of Repetitive DNAs in the Saffron Finch, Sicalis flaveola (Passeriformes, Aves) - Rafael Kretschmer (Animals, 2021)
The Saffron finch (Sicalis flaveola), a semi-domestic species, is tolerant of human proximity and nesting in roof spaces. Considering the importance of cytogenomic approaches in revealing different aspects of genomic organization and evolution, we provide detailed cytogenetic data for S. flaveola, including the standard Giemsa karyotype, C- and G-banding, repetitive DNA mapping, and bacterial artificial chromosome (BAC) FISH. We also compared our results with the sister groups, Passeriformes and Psittaciformes, bringing new insights into the chromosome and genome evolution of birds. The results revealed contrasting rates of intrachromosomal changes, highlighting the role of SSR (simple short repetition probes) accumulation in the karyotype reorganization. The SSRs showed scattered hybridization, but brighter signals were observed in the microchromosomes and the short arms of Z chromosome in S. flaveola. BACs probes showed conservation of ancestral syntenies of macrochromosomes (except GGA1), as well as the tested microchromosomes. The comparison of our results with previous studies indicates that the great biological diversity observed in Passeriformes was not likely accompanied by interchromosomal changes. In addition, although repetitive sequences often act as hotspots of genome rearrangements, Passeriformes species showed a higher number of signals when compared with the sister group Psittaciformes, indicating that these sequences were not involved in the extensive karyotype reorganization seen in the latter.